Ways of ensuring the efficiency of the educational process in combat conditions - Riabchykov, M.; Riabchykova, O.; Alexandrov , A.; Korolyova, N. (Problems of Engineer-Pedagogical Education, 2023)
The study is devoted to the problems of teaching and learning during hostilities and other dangerous situations that lead to mass displacement of people. The real situation in Ukraine in 2022 was taken into account. The relevance of Ukraine's accession to the declaration of safe schools is described. The main problems of education during hostilities, which are associated with the destruction of educational facilities and forced displacement of teaching personnel and students, are identified. The main tasks of education, requirements for teachers, as well as peculiarities of teaching and learning during military operations and other dangerous situations are revealed. The main organizational problems characteristic of the system of secondary and higher education are highlighted. Structures of the organization of education, which can be stable and unstable during dangerous situations, are defined and described; recommendations for increasing stability are given. The impact of authoritarian or democratic management in schools, and the importance of the basic principles that govern the school when working during dangerous situations are emphasized. Based on a study of 527 students and 58 teachers of secondary and higher education institutions, the main places of displacement of refugees in Ukraine and abroad are determined. The dynamics of students attending classes in the conditions of distance learning and the change in the effectiveness of training are determined. Studies prove that displaced students attend education institutions much less often. At the same time, there is an additional psychological burden, as well as difficulties in communication. Findings show that there exists a limit to the real participation of students in the learning process in the conditions of involvement of the efforts of teachers and supervisory bodies of the education institution. Features of the teaching methodology during military operations and other dangerous situations are described. The need to include components aimed at giving students psychological relief onto the list of educational components is identified. At the same time, components related to humanitarian issues should take at least 15-25%. The methods of verbal and non-verbal online discussions to increase the effectiveness of training in contexts stricken by military conflict are described. In particular, this refers to mathematical, technical and other competencies that require an active approach.